El derecho al voto facultativo para las personas ecuatorianas entre dieciséis y dieciocho años de edad - Garrido Herrera, Patricia Margarita (2013)
From the Convention on the Rights of the Child in 1990, was created the Doctrine of Integral Protection which considers the children and adolescents as subjects of all human rights, which are gradually exercising them. Following Pisarello Aparicio (2008), Joaquín Herrera (2008) and Perez Luño (1999) states that human rights are tangible or intangible prerogatives that children and teenagers need to meet to live in dignity. In this way a form of exercise human rights are the rights of participation that consist in linking the adolescents in matters of public interest. Therefore, from the new Constitution of the Republic of Ecuador, enacted in 2008, is in effect optional voting rights of the adolescents between sixteen and eighteen years of age in accordance with Article 62.2, for this reason they hold this law faculty who participate in matters of public interest gradually. Finally, this research evidence that adolescents are able to exercise this right, and, are interested in matters of public interest. For both there is a reasoned vote, conscious and responsible stewardship necessary state, society and family. So this research is that the Ecuadorian state has partially fulfilled its obligations. Thus this thesis proposes that, for the exercise of voting rights in a reasoned optional, aware and responsible is necessary that the state promote information about this right, as well as civic education on human rights to all adolescents nationwide without any limitation. In a way that generates a civic responsibility and strengthen democracy.